ISLAMIC BRANDING ASINAN BETAWI MAK HAJI - Agus Hermanto; Sa’diyah EL Adawiyah; Tria Patranti (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2022)
Islamic branding as one of the strategies is a necessity, to be able to enter the Indonesian market which is so large with its Muslim community. Strategies carried out on brands that describe Islamic identity. This research tries to look at various aspects of marketing communication related to branding through Islamic branding from Asinan Betawi Mak Haji. The research formula is, How about Islamic Branding Asinan Betawi Mak Haji? with research purposes; 1) The form of branding Asinan Betawi Mak Haji; 2) Islamic branding Asinan Betawi Mak Haji. The research used is qualitative methods with narrative analysis in expressing and analyzing how the communicator tells a story objectively from 1 (one) key informant and 2 (two) informants including triangulation. The conclusion was that the Asinan Betawi business began in 2018, which at that time did not yet have a brand and promotional activities and product marketing through social media Facebook and Instagram. There are 5 (five) forms of Asinan Betawi Mak Haji branding to differentiate the product from others. The word 'Mak Haji' which is translated into visual identity is a logogram and adds the MAK HAJI logotype to strengthen the brand identity, which reflects the vision, personality and existence of Islamic branding. It is hoped that this research will be useful to provide references as well as input and consideration for further research and activists of the halal industry in building Islamic branding.